Activities Management of Ethical Socialization in Young Buddhist at Buddhapadipa Dhamma Retreat Suphanburi Province - Yaemsuksawat, Yuphadee; Phusuwan , Sathaphon; Wiyaboon, Saowanee (Journal of Dhamma for Life, 2025)
The purposes of this dissertation were: 1) To study the participation of homes, temples, and schools to design ethical socialization activities for the young Buddhist and 2) To study the management of ethical socialization activities for the young Buddhist at Buddhapadipa Dhamma Retreat Suphanburi province. Methodology: This research was qualitative research. The sampling of this research consisted of the monk 1 person, the leaders of activity 4 people, teachers 5 people and villagers 10 people; total 20 people. The research methods consisted of in-depth interview and data analyze by content analysis. Main Results: The results were found that: 1) Family Unit is the most important to socialization process. The young Buddhist can apply the principles gained from Buddhist activities in their daily lives. It teaches the basics such as the gratitude and the five precepts which the family's care can help socialization and provide advice. 2) Educational Unit incorporate Buddhist principles into teaching and learning. Including cooperation with family unit and religious unit in communicating the behavior of the young Buddhist for socialization through Buddhist activities 3) Religion Unit; Monks are the ones who transmit principle which are important anchors in daily life. It will focus on putting Buddhist principle into practice which starts with having basic gratitude to their parents and practice follow the 5 precepts regularly.